Systematic Literature Review Penilaian Kinerja Warehouse - Adhisty Kartika Dewi (JERA : Journal of Engineering Research and Application, 2025)
The development of industry in Indonesia is now an interesting topic of discussion among practitioners and academics. The Manufacturing Industry is one of them, this industry has several very promising commodities. The dynamic nature of the manufacturing industry makes industry players, in this case manufacturing companies, to be able to survive and increase company productivity. Increasing productivity is closely related to the efforts taken by the company, including performance measurement. Performance measurement is not only in the production section, performance measurement can also be done in the Warehouse. Warehouse performance measurement or commonly called warehouse Performance is the objective of this study. The method used is a literature study in the form of journals and proceedings as many as 25 articles. This study is an effort to map the conditions of previous research on Warehouse peer performance. Based on the analysis that has been done, warehouse performance using the KPI and AHP methods for manufacturing companies has the potential for further research. In addition, according to the analysis that has been done, warehouse performance can produce tactical and strategic decisions that are useful in the development of manufacturing companies in the future. Keywords: warehouse performance, KPI, AHP, Industri Manufaktur